1985
DOI: 10.1111/j.1365-2265.1985.tb00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprecipitation of Tsh‐tsh Receptor Complexes

Abstract: The ability of Graves' sera to interact with the TSH receptor crosslinked to a 125I-labelled photoactive derivative of TSH has been investigated. Crosslinked complexes were prepared using non-purified detergent solubilized human thyroid and guinea pig fat TSH receptors. Affinity purified porcine TSH receptor preparations wee also used. After crosslinking, the crosslinked TSH-TSH receptor complexes were separated from aggregates and free TSH on Sephacryl S-300, incubated with test sera followed by immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…These observations were based on the use of gel filtration to assess the size of the complexes formed between labeled TSH, detergent-solubilized TSH receptors, and TRAb. Petersen et al (113), Rickards et al (10), and Parkes et al (114) confirmed and extended these observations. No termolecular complex consisting of labeled TSH, the TSH receptor, and TRAb could be detected using immunoprecipitation or gel filtration.…”
Section: Characteristics Of the Tsh Receptor-trab Interactionsupporting
confidence: 54%
See 2 more Smart Citations
“…These observations were based on the use of gel filtration to assess the size of the complexes formed between labeled TSH, detergent-solubilized TSH receptors, and TRAb. Petersen et al (113), Rickards et al (10), and Parkes et al (114) confirmed and extended these observations. No termolecular complex consisting of labeled TSH, the TSH receptor, and TRAb could be detected using immunoprecipitation or gel filtration.…”
Section: Characteristics Of the Tsh Receptor-trab Interactionsupporting
confidence: 54%
“…This indicates that charge-charge interactions will be of major importance 114 REES SMITH ET AL. in the binding of hormone or antibody to the TSH receptor A subunit.…”
Section: Charge-charge Interactions and The Tsh Receptormentioning
confidence: 95%
See 1 more Smart Citation
“…These results suggest that TRAb crossreacts with TSH receptors on rat fat membranes. A significant correlation between the inhibition activities of Graves' IgG on TSH binding to guinea pig fat and human or porcine thyroid membranes was reported (Kishihara et al 1979b;Parkes et al 1985). From these findings it is conceivable that TRAb is not species specific as reported by Davies (1981) and Strakosch et al (1982).…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, Kohn et al (1983) proved the existence of TSH-receptor antibodies which did not inhibit TSH-binding by using mouse-mouse hybridoma. On the other hand, Parkes et al (1985) who studied the interaction between Graves' sera and that TSH-binding and TSH-receptor antibody binding were mutually exclusive. The reason for the discrepancy is not clear at present.…”
Section: Radioiodination Of Tshmentioning
confidence: 99%